Exploring the meaning of significance in experimental economics - Zhang, Lyla; Ortmann, A. (University of New South Wales, 2013)
Null Hypothesis Significance Testing has been widely used in the experimental economics literature. Typically, attention is restricted to type-I-errors. We demonstrate that not taking type-II errors into account is problematic. We also provide evidence, for one prominent area in experimental economics (dictator game experiments), that most studies are severely underpowered, suggesting that their findings are questionable. We then illustrate with several examples how poor (no) power planning can lead to questionable results.